1990
DOI: 10.5694/j.1326-5377.1990.tb126198.x
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of suicide

Abstract: The prediction of suicide remalns a major challenge for health professionals. Sociodemographic predictors of the risk of suicide lack specificity: factors such as living alone, being unemployed, or having a physical or mental iliness are common, separately or in combination, but suicide is rare. Psychiatric conditions, such as depression, alcohol dependence, schizophrenia and personality disorders, are strongly associated with sUicide, but most psychiatrically ill patients do not suicide. Most suicidal patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…It is important to have social contacts and close friends, i.e. people who can give a helping hand or advice, as well as people to trust (11)(12)(13). Lack of social support is one of the suicide risk factors in the SAD PERSONS scale (14).…”
mentioning
confidence: 99%
“…It is important to have social contacts and close friends, i.e. people who can give a helping hand or advice, as well as people to trust (11)(12)(13). Lack of social support is one of the suicide risk factors in the SAD PERSONS scale (14).…”
mentioning
confidence: 99%
“…Similarly, in the present study, the number of suicide attempts were higher in women than in men and 1 person who died due to a suicide attempt was male. Also, being single acts as a risk factor for a suicide attempt (9). Consistently, it was found that suicide attempts were higher in singles.…”
Section: Discussionmentioning
confidence: 58%
“…The influence of substance abuse as a risk factor has been shown to vary with disorder type, age and sex. For example, illicit drug abuse heightens the risk of suicide for young men, licit drug addiction enhances the risk for young women and alcoholism increases the risk for older men [17,18]. It is often regarded as a distal or long‐term risk factor, but can also be considered to heighten suicide risk proximally or in the short term (e.g.…”
Section: Discussionmentioning
confidence: 99%